1997
DOI: 10.2337/diacare.20.5.760
|View full text |Cite
|
Sign up to set email alerts
|

The Problem Areas in Diabetes Scale: An evaluation of its clinical utility

Abstract: The study findings provided support for the construct validity of the PAID, including evidence for discriminant validity from its ability to detect differences between IDDM and NIDDM treatment groups expected to differ in the emotional impact of life with diabetes. Future studies should explore the PAID's performance in nonspecialist treatment settings as well as its responsiveness to clinical change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
472
3
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 560 publications
(500 citation statements)
references
References 0 publications
20
472
3
5
Order By: Relevance
“…The scale has proved to be a useful measure to assess diabetes-related distress, and its responsiveness has been tested, supporting its sensitivity to change over time (Welch et al, 2003). Empirical studies have demonstrated the PAID to display good psychometric properties and to correlate strongly with a wide range of theoretically related constructs such as for example general emotional distress, depression and diabetes self-care behavior (Polonsky et al, 1995;Snoek et al, 2000a;Welch et al, 1997). The scale was originally not conceptualized as a multi-domain scale (Polonsky et al, 1995).…”
Section: Measures 231 Diabetes-related Distressmentioning
confidence: 99%
See 2 more Smart Citations
“…The scale has proved to be a useful measure to assess diabetes-related distress, and its responsiveness has been tested, supporting its sensitivity to change over time (Welch et al, 2003). Empirical studies have demonstrated the PAID to display good psychometric properties and to correlate strongly with a wide range of theoretically related constructs such as for example general emotional distress, depression and diabetes self-care behavior (Polonsky et al, 1995;Snoek et al, 2000a;Welch et al, 1997). The scale was originally not conceptualized as a multi-domain scale (Polonsky et al, 1995).…”
Section: Measures 231 Diabetes-related Distressmentioning
confidence: 99%
“…According to de Groot et al (2010), such problems are more prevalent among people with type 2 diabetes than in those of the general population. Moreover, diabetes-related distress has mainly been studied in relation to diabetesmanagement and metabolic control and, to some extent, in relation to perceived social support (Lloyd et al, 2005;Polonsky et al, 1995;Snoek et al, 2000a;Welch et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PAID-SP was developed from the Hispanic version [7] with minor changes in the wording of Page 4 of 11 A c c e p t e d M a n u s c r i p t some items. Although the exploratory factor analysis of the original version suggested one general 20-item factor [14] some of the following studies have proposed alternative factor structures based on two, three or four factors [6,8,10].…”
Section: Participants and Measuresmentioning
confidence: 99%
“…PAID is a reliable and validated questionnaire [45] which measures diabetes-specific emotional distress related to living with and managing diabetes including guilt, fear, anger, depressed mood and worry [46]. Participants answer 20 questions using a Likert scale with for greater diabetes related distress [47].…”
Section: Problems Areas In Diabetes (Paid)mentioning
confidence: 99%